2005
DOI: 10.1158/0008-5472.can-04-1554
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Homocysteine Junction Enzymes in the NCI60 Panel of Human Cancer Cell Lines

Abstract: Methionine metabolism provides two key cellular reagents: S-adenosylmethionine and glutathione, derived from the common intermediate, homocysteine. A majority of cancer cells exhibit a methionine-dependent phenotype whereby they are unable to grow in medium in which methionine is replaced by its precursor, homocysteine. Additionally, CpG island hypermethylation of tumor suppressor gene promoters is observed in a background of global hypomethylation in cancerous cells. In this study, we have profiled the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 40 publications
3
32
1
Order By: Relevance
“…Several studies addressed the expression profiles and polymorphisms of enzymes involved in methionine metabolism, including CBS in gastric cancer (25), cancer cell lines (26), biliary tract cancer (27), bladder cancer (28), colorectal cancer (29,30), breast cancer (31), and liver cancer (7,8). However, the molecular basis of altered methionine metabolism and its role in carcinogenesis have not been clarified and the connection is likely to be complex and dependent on the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies addressed the expression profiles and polymorphisms of enzymes involved in methionine metabolism, including CBS in gastric cancer (25), cancer cell lines (26), biliary tract cancer (27), bladder cancer (28), colorectal cancer (29,30), breast cancer (31), and liver cancer (7,8). However, the molecular basis of altered methionine metabolism and its role in carcinogenesis have not been clarified and the connection is likely to be complex and dependent on the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were washed three times with cold PBS, resuspended in PBS, and then harvested and lysed by suspending in lysis buffer as described previously (17,18). MS, CBS, and actin levels in cell extracts were determined using the respective primary and secondary antibodies and detected using the chemiluminescent horseradish peroxidase system (Sigma) as described previously (17,18). The intensity of protein bands was quantified using the Quantity One software (Bio-Rad) and normalized to the actin level in the same sample.…”
Section: Methodsmentioning
confidence: 99%
“…In an expression profiling survey, conducted in 2005, most cell lines of the NCI60 collection of human cancer cell exhibited increased CBS expression (assessed by Western blot analysis), with the highest expression levels noted in breast, ovarian, and renal cancer lines (146). In a more recent study, the prostate cancer cell lines LNCaP, PBH-1, and DU145 showed a marked increase in CBS expression, which correlated with increased H 2 S production (39).…”
Section: Increased Expression Of Cbs And/or Increased Production Of Hmentioning
confidence: 99%